Analisis Pengaruh Inflasi, Nilai Tukar Idr/Usd, Sertifikat Bank Indonesia Syariah (Sbis), Harga Minyak Dunia Terhadap Indeks Saham Syariah Indonesia (Issi)Periode Desember 2011 - November 2016 - Karnasih, Niken; , Dr. Didit Purnomo, MSi; , Drs. Harun, M.H (2017)
Indonesian Sharia Stock Index (Indeks Saham Syariah Indonesia (ISSI)) is one of sharia stock index in Indonesia which reflects the entire sharia stocks listed in The Indonesian Stock Exchange (Bursa Efek Indonesia (BEI)) to count the average stock with types of stocks that meet the criteria of sharia. This research aims to know the influences of macroeconomic variables comprising of inflation, Exchange Rate of IDR/USD, Certificate of Indonesian Sharia Bank (Sertifikat Bank Indonesia Syariah (SBIS)), the World Oil Price on the Indonesian Sharia Stock Index (ISSI) in period of December 2011 - November 2016. Type of data used in this research are secondary data in the form of monthly time series. The method of analysis in this research used quantitative analysis and the analysis tool used is Error Correction Model (ECM) processed by using Eviews7 software. The results of this research revealed that the variable of Exchange Rate of IDR/USD in short term and long term had a significant influence on the Indonesia Sharia Stock Index (ISSI). Meanwhile, the results of the error correction model revealed that in the short term, the variable of Exchange Rate of IDR/USD had a significant influence on the Indonesian Sharia Stock Index (ISSI). In the long term, the variables of inflation, Exchange Rate of IDR/USD, Certificate of Indonesian Sharia Bank (SBIS), and the World Oil Price had a significant influence on the Indonesian Sharia Stock Index (ISSI). Keywords: Indonesian Sharia Stock Index (ISSI), Inflation, Exchange Rate of IDR/USD, Certificate of Indonesian Sharia Bank (SBIS), the World Oil Price.